Menyoal Tubuh dan Kehadiran dalam Mediasi Liturgi ke Ruang Digital - Putra Arliandy (THRONOS: Jurnal Teologi Kristen, 2023)
This article discusses the challenge faced by liturgy as a ritual that embodies physical presence in adapting to the digital realm catalyzed by the COVID-19 pandemic in early 2020. Amidst various models of liturgy that emerged due to this mediation, the issue of body and presence became a debate between pro-digital and contra-digital groups. One point of contention was whether worship without physical gathering in a specific location could be considered incarnational. To address this issue, this article presents Daniella Zsupan-Jerome's perspective on sacramental presence in the digital space, which will be connected with liturgical approaches, specifically through the theological-symbolic perspective of Emmanuel Martasudjita. Using a literature review method, Zsupan-Jerome's arguments, rooted in the thoughts of Louis-Marie Chauvet and Jean-Luc Marion, will be discussed with the help of other scholars who have previously explored the theme of the body and its presence in the digital space. The theological discourse built from this discussion is expected to provide an alternative perspective for readers in the post-pandemic era, encouraging them not to perceive digital worship solely as a disembodied experience that creates a shallow presence. However, it does not necessarily intend to promote digital worship as a better option than in-person worship. AbstrakLiturgi sebagai sebuah ritual yang menubuh menghadapi tantangan berupa mediasi ke ruang digital yang dikatalisasi oleh pandemi COVID-19 pada awal 2020 silam. Di tengah berbagai model liturgi yang muncul sebagai akibat dari mediasi tersebut, tubuh dan kehadiran menjadi isu yang diper-debatkan antara kelompok yang pro dan kontra-digital. Salah satu poin perdebatannya adalah apakah sebuah ibadah yang berlangsung tanpa pertemuan fisik pada satu lokasi tertentu dapat disebut inkarnasional atau tidak. Dalam rangka menjembatani persoalan tersebut, artikel ini menyajikan pandangan Daniella Zsupan-Jerome tentang kehadiran sakramental dalam ruang digital yang kemu-dian akan dihubungkan juga dengan pendekatan liturgi, secara khusus melalui perspektif teologi simbol menurut Emmanuel Martasudjita. Dengan menggunakan metode tinjauan literatur, argumen-tasi Zsupan-Jerome yang dilatarbelakangi oleh pemikiran Louis-Marie Chauvet dan Jean-Luc Marion, akan dibahas dengan bantuan tokoh lainnya yang telah terlebih dahulu menggumuli tema mengenai tubuh dan kehadiran dalam ruang digital. Wacana teologis yang terbangun pada akhirnya diharapkan dapat menjadi alternatif bagi pembaca di masa post-pandemic agar tidak terus-menerus melihat ibadah digital sebagai sebuah pengalaman yang tidak bertubuh dan hanya menciptakan sebuah kehadiran dangkal, sekalipun tidak serta-merta bermaksud untuk mengunggulkan opsi ibadah digital dari iba-dah yang berlangsung secara tatap muka.